Effects of whole seaweed consumption on humans: current evidence from randomized-controlled intervention trials, knowledge gaps, and limitations - Trigo, João P.; Palmnäs-Bédard, Marie; Juanola, Mar Vall-Llosera; Undeland, Ingrid (Frontiers in Nutrition, 2023)
Seaweed is often recognized for its potential health benefits, attributed to its abundance of dietary fibers, protein, and polyphenols. While human observational studies have shown promise, the collective evidence from human intervention trials remains limited. This narrative review aims to comprehensively analyze the effects of seaweed intake on humans, while critically assessing the methodology, including Cochrane risk-of-bias assessment. A search was conducted in online databases, including PubMed, Scopus, and Google Scholar, covering the period from 2000 to May 2023. The focus was on randomized controlled clinical trials (RCTs) evaluating the impact of whole seaweed, either consumed as capsules, integrated into food products or as part of meals. Various health outcomes were examined, including appetite, anthropometric measures, cardiometabolic risk factors, thyroid function, markers of oxidative stress, and blood mineral concentrations. Out of the 25 RCTs reviewed, the findings revealed limited yet encouraging evidence for effects of seaweed on blood glucose metabolism, blood pressure, anthropometric measures, and, to a lesser extent, blood lipids. Notably, these favourable effects were predominantly observed in populations with type-2 diabetes and hypertension. Despite most trials selecting a seaweed dose aligning with estimated consumption levels in Japan, considerable variability was observed in the pretreatment and delivery methods of seaweed across studies. Moreover, most studies exhibited a moderate-to-high risk of bias, posing challenges in drawing definitive conclusions. Overall, this review highlights the necessity for well-designed RCTs with transparent reporting of methods and results. Furthermore, there is a need for RCTs to explore seaweed species cultivated outside of Asia, with a specific emphasis on green and red species. Such studies will provide robust evidence-based support for the growing utilization of seaweed as a dietary component in regions with negligible seaweed consumption e.g., Europe.